Topical Bethanechol for the Improvement of Esophageal Dysmotility: A Pilot Study. (August 2013) - O'Rourke, Ashli; Weinberger, Paul; Morrison, Michele; Conklin, Jeffrey; Postma, Gregory
Objectives: We studied a case series to evaluate the effect of topical bethanechol chloride on esophageal function in individuals with ineffective esophageal motility. Methods: Five subjects with ineffective esophageal motility underwent high resolution esophageal manometry. Ten 5 mL liquid swallows were performed to establish a baseline. Five milligrams of topical bethanechol was then administered. After 10 minutes, the subjects completed 10 additional liquid swallows. This procedure was repeated with 10 mg of bethanechol in 4 subjects. Results: After administration of 5 mg of topical bethanechol, the mean (±SD) distal contractile integral, an index of esophageal contractility, increased from 178.3 ± 83.1 mm Hg·s·cm to 272.3 ± 216.9 mm Hg·s·cm (p = 0.69). The percentage of failed swallows decreased from 52.8% ± 33.2% to 29.4% ± 18.3% (p = 0.14). The percentage of peristaltic swallows increased from 28.0% ± 26.8% to 67.2% ± 15.3% (p = 0.04). The contractile front velocity was essentially unchanged. After administration of 10 mg of bethanechol, the distal contractile integral decreased from 349.3 ± 371.0 mm Hg·s·cm to 261.8 ± 293.5 mm Hg·s·cm (p = 0.72). The percentage of failed swallows increased from 57.5% ± 37.7% to 66.8% ± 24.9% (p = 0.46). The percentage of peristaltic swallows increased from 17.5% ± 23.6% to 28.3% ± 19.1% (p = 0.29). The contractile front velocity decreased from 11.6 ± 5.2 cm/s to 4.9 ± 3.0 cm/s (p = 0.32). No adverse side effects occurred. Conclusions: The results of this pilot study support the need for further investigation with larger sample sizes and dose escalation.